Kultivasi Mikroalga Chlorella dengan Media Air Limbah (Studi Literatur untuk Produksi Biomassa dan Pengolahan Air Limbah) - Darwin Darwin; Anshah Silmi Afifah; Gita Prajati (Fakultas Teknik, 2023)
Chlorella is a microalga that has been extensively used because of its fast-growing ability and can reduce pollutant in the wastewater as well. By using wastewater as a nutrient source for Chlorella cultivation, it has a potential to accomplish a sustainable biomass production. In this literature review, the ability of Chlorella to reduce pollutant (COD, TN, TP) in the wastewater were summarized. The average of pollutant removal of COD, TN and TP by Chlorella are 70,4%; 80%; and 79,4%. The biomass productivity of Chlorella cultivated in the wastewater reach 450 mg/L/day. In the end, there are some additional treatments that is used to enhance the Chlorella growth and the pollutant removal performance. Those additional treatments are surfactant, glycerol, pre-treatment and diluting wastewater concentration.